Empowering Students towards Self-Directed Learning Using Multiple Choice Questions Construction as a Learning Tool in a Private Medical College: A Mixed Quantitative and Qualitative Study - Nilofar Mustafa; Shazia Tufail; Maria Ahmad; Qurat ul Ain Mushtaq; Pakeeza Aslam; Riffat Sarwar (Life and Science)
Objective: To determine the effectiveness of Multiple Choice Questions (MCQ) construction as a learning tool for empowering the students towards self-directed learning. Study Design: Mixed quantitative and qualitative study. Place and Duration of Study: The study was carried out at Department of Obstetrics and Gynaecology, CMH st th Lahore Medical College, from 1 April to 30 September 2019. Materials and Methods: All students of final year MBBS were divided into two groups. After a pre-test (test 1) of MCQs, they attended a workshop on construction of MCQs, followed by construction and vetting of MCQs by students. The students took a test (test 2) based on those MCQs and evaluated it, followed by post-test (test 3) 08 weeks later to assess deep learning. Semi structured in-depth interviews of 10 randomly selected students based on 10 open ended questions were conducted about their perceptions of learning. Quantitative data analysis was performed using SPSS version 17. A thematic analysis was performed for the qualitative data. Results: Comparison of pre and post-tests yielded a p value of 0.013, which is statistically significant. Comparison of the mean results of tests 1 and 2 yielded a p value of 0.001, which is also statistically significant. The qualitative component of the study revealed that use of MCQ construction to enhance self-directed learning was highly appreciated by the students as a learning tool. Conclusion: MCQ construction when used as a learning tool improved the self-directed learning of the students. Experience of construction of MCQs enhanced the cognitive skills of the students while being highly acceptable.